2014
DOI: 10.1016/j.ecolecon.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Product level embodied carbon flows in bilateral trade

Abstract: As increasingly complex modelling approaches to quantifying embodied carbon in trade have become popular, the lack of disaggregation has been identified as a key weakness. This paper quantifies embodied carbon in bilateral trade at the product level. This is done using the material balance approach, by collecting product carbon intensity factors from multiple data sources and combining with bilateral trade data in physical quantities. The dataset covers trades between 195 countries for 1080 products in 2006. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Our work also relates to the literature on the carbon content of trade (Sato, 2014;Aichele & Felbermayr, 2015). Looking at the Kyoto protocol, Aichele & Felbermayr (2015) estimate that trade flows increased by 5% and embodied carbon emissions by 8% between committed and non-committed trade partners after Kyoto was signed.…”
Section: Introductionmentioning
confidence: 77%
“…Our work also relates to the literature on the carbon content of trade (Sato, 2014;Aichele & Felbermayr, 2015). Looking at the Kyoto protocol, Aichele & Felbermayr (2015) estimate that trade flows increased by 5% and embodied carbon emissions by 8% between committed and non-committed trade partners after Kyoto was signed.…”
Section: Introductionmentioning
confidence: 77%
“…International cooperation on reducing trade-embodied and total impacts worldwide is the only way to tackle unsustainability at the national scale. Sato ( 2014 ) found that the lion's share of global carbon emissions emb odied in trade is concentrated in a relatively small number of product categories of traded goods (amongst the top ten in 2006 were motor spirit (gasoline/petrol), steel, aluminium, motor vehicles, ships/boats and Portland cement). This suggests that focusing trade and mitigation policies on these products may be an effective strategy to tackle at least the pressing issue of global warming.…”
Section: Is Trade Good or Bad? Some Final Thoughtsmentioning
confidence: 99%
“…What these methods have all in common is the inclusion of both direct and indirect energy needs for individual products or services. Although this micro‐level approach has numerous limitations, it allows an analysis of the actual flows of energy at a level of individual products (Sato , ). The major constraint of this micro‐level approach is then the extensive data need especially on the carbon and energy intensity factors.…”
Section: Previous Research and Methodological Considerationsmentioning
confidence: 99%
“…The major constraint of this micro‐level approach is then the extensive data need especially on the carbon and energy intensity factors. Interestingly, an analysis of global carbon flows of 1,080 products showed that some 10% of the products are responsible for 70% of the emissions embodied in trade (Sato ).…”
Section: Previous Research and Methodological Considerationsmentioning
confidence: 99%